2002
DOI: 10.4049/jimmunol.168.2.816
|View full text |Cite
|
Sign up to set email alerts
|

The Bacterial Peptide N-Formyl-Met-Leu-Phe Inhibits Killing of Staphylococcus epidermidis by Human Neutrophils in Fibrin Gels

Abstract: To study human neutrophil (polymorphonuclear leukocyte (PMN)) migration and killing of bacteria in an environment similar to that found in inflamed tissues in vivo, we have used fibrin gels. Fibrin gels (1500 μm thick) containing Staphylococcus epidermidis were formed in Boyden-type chemotaxis chambers. PMN migrated <300 μm into these gels in 6 h and did not kill S. epidermidis when the gels contained heat-inactivated serum, C5-deficient serum, a streptococcal peptidase specific for a fragment of cleave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 56 publications
(58 reference statements)
2
16
0
Order By: Relevance
“…Previous studies (13) showed that incubation of S. epidermidis H753 with human serum opsonized these bacteria with IgG and the C3 component of complement, and that opsonization with both IgG and C3 is required for killing in suspension by neutrophils. We used this system to assess whether killing of S. epidermidis by neutrophils depends on the neutrophil concentration or the ratio of neutrophils to bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies (13) showed that incubation of S. epidermidis H753 with human serum opsonized these bacteria with IgG and the C3 component of complement, and that opsonization with both IgG and C3 is required for killing in suspension by neutrophils. We used this system to assess whether killing of S. epidermidis by neutrophils depends on the neutrophil concentration or the ratio of neutrophils to bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Complement component C5a is important for rapid neutrophil recruitment to the sites of streptococcal infection [11] and is required for neutrophil-mediated bacterial killing [12]. C5a peptidase (SCPA), a surface virulence factor, is highly conserved among GAS serotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Following two serial 10-fold dilutions in sterile water, 50 μL of the sonicated solution was added to bacterial TSB agar plates and incubated at 37°C. The bacterial colonies that formed were counted after 48 hour [14], [15]. At these dilutions, control plates incubated in the absence of neutrophils usually contained approximately 2,000 colonies, or 10 7 bacteria per disc.…”
Section: Methodsmentioning
confidence: 99%